Bubble contagion: Evidence from Japan's asset price bubble of the 1980-90s - Hu, Y.; Oxley, Leslie (2018)
© 2018 This paper investigates the most documented asset price bubbles of the 1980-90s in Japan, and subjects them to the rigours of recent econometric tests. We focus on testing for bubbles in Japan's stock and real estate markets from 1970Q1 to 1999Q4 using the right-tailed unit root test of Phillips et al. (2015a, PSY). We also utilize the econometric methods of Greenaway-McGrevy and Phillips (2016) to explore the possibility of contagion between these two markets. The paper offers significant econometric-based evidence of bubbles in both markets during this period in Japan and more importantly, for the first time in the literature, formal tests of bubble contagion from Japan's stock market to its real estate market. Our findings may help to understand why Japan's real estate bubble collapsed after the stock price bubble, as the bubble-like behaviour from the stock market migrates to the real estate market.